Cost-effectiveness of Mindfulness-based Stress Reduction Versus Cognitive Behavioral Therapy or Usual Care Among Adults With Chronic Low Back Pain. Issue 20 (15th October 2017) - Herman, Patricia M.; Anderson, Melissa L.; Sherman, Karen J.; Balderson, Benjamin H.; Turner, Judith A.; Cherkin, Daniel C.
Abstract : Study Design: Economic evaluation alongside a randomized trial of cognitive-behavioral therapy (CBT) and mindfulness-based stress reduction (MBSR) versus usual care alone (UC) for chronic low back pain (CLBP). Objective: To determine 1-year cost-effectiveness of CBT and MBSR compared to 33 UC. Summary of Background Data: CLBP is expensive in terms of healthcare costs and lost productivity. Mind-body interventions have been found effective for back pain, but their cost-effectiveness is unexplored. Methods: A total of 342 adults in an integrated healthcare system with CLBP were randomized to receive MBSR (n = 116), CBT (n = 113), or UC (n = 113). CBT and MBSR were offered in 8-weekly 2-hour group sessions. Cost-effectiveness from the societal perspective was calculated as the incremental sum of healthcare costs and productivity losses over change in quality-adjusted life-years (QALYs). The payer perspective only included healthcare costs. This economic evaluation was limited to the 301 health plan members enrolled ≥180 days in the years pre-and postrandomization. Results: Compared with UC, the mean incremental cost per participant to society of CBT was $125 (95% confidence interval, CI: −4103, 4307) and of MBSR was −$724 (CI: −4386, 2778)—that is, a net saving of $724. Incremental costs per participant to the health plan were $495 for CBT over UC and −$982 for MBSR, and incremental back-related costs per participant were $984 for CBT over UC and −$127 for MBSR. These costs (and cost savings) were associated with statistically significant gains in QALYs over UC: 0.041 (0.015, 0.067) for CBT and 0.034 (0.008, 0.060) for MBSR. Conclusion: In this setting CBT and MBSR have high probabilities of being cost-effective, and MBSR may be cost saving, as compared with UC for adults with CLBP. These findings suggest that MBSR, and to a lesser extent CBT, may provide cost-effective treatment for CLBP for payers and society. Level of Evidence: 2